Pengaruh Pengendalian Internal, Moralitas Manajemen, Kesesuaian Informasi, Dan Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi - Nadia, Fatma; Zanaria, Yulita; Sari, Gustin Padwa (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the effect of internal control, management morality, conformity of information, and compliance with accounting rules on the tendency of accounting fraud (Empirical Study at PT Pelindo Lampung Selatan). This type of research is quantitative research. The instruments used in this study were questionnaires and observations. The data analysis technique performed is using multiple regression analysis. The results of the study show that Internal Control has a significant effect on accounting fraud. Management morality has a significant effect on accounting fraud. Information suitability has a significant effect on accounting fraud. Compliance with accounting rules has a significant effect on accounting fraud. Internal Control, Management Morality and Information Conformity simultaneously have a significant effect on accounting fraud